Economic and Monetary Union: insights into the theoretical conundrum of European Integration - Vila Maior, Paulo (2010)
As part of an ongoing research, this paper focus on European monetary integration depicting to what extent existing theories and theoretical approaches fit with the ontology and subsequent developments of Economic and Monetary Union (EMU). A special emphasis goes to the Stability and Growth Pact (SGP) as a crucial ingredient of European monetary integration, particularly for the political turmoil it produced in recent years. On a previous conference (UACES Annual Conference 2007: Exchanging Ideas on Europe: Common Values and External Policies, Portsmouth, UK, 3-5 September 2007), EMU and the SGP were assessed through the lens of neofunctionalism, liberal intergovernmentalism, supranational governance, new institutionalism and the fusion thesis. This paper turns to the federal theory and the rational choice theory. Some argue that the power of ideas (the monetarist school) and national governments’ adjustment to a new international setting provide the broad explanation of the move towards EMU. Others claim that the project of European monetary integration was independent from such exogenous inputs, understanding the step towards EMU as part of the dynamism encapsulated by European integration. I test these contrasting perceptions against the explanatory power of federal theory and rational choice. The analysis of the SGP (in both the original version and after the November 2005 reform) follows the same methodology. The rationale behind the paper is twofold. On the one hand, whether EMU and the SGP fit into one of the theories under examination, and whether the corresponding mapping is telling of theoretical prevalence or dissemination. On the other hand, whether the SGP (and subsequent reform) converges or diverges with EMU’s theoretical matrix.